Subunit interaction in cyclic AMP-dependent protein kinase of mutant lymphoma cells. - Hochman, J (1977)
We have previously selected and characterized mutant S49 mouse lymphoma cells that possess an adenosine 3':5'-cyclic monophosphate (cAMP)-dependent protein kinase (ATP:protein phosphotransferase, EC 2.7.1.37) with an increased apparent affinity constant (Ka) for activation by cAMP. The Ka lesion in one such mutant clone has been shown to result from a structural mutation involving the kinase holoenzyme's regulatory (R) subunit. The present report examines the interaction of R and catalytic (C) subunits of the kinases in extracts of the mutant cells and the normal "wild type" (WT) parental line. Subunit recombination experiments were performed, by using purified WT and mutant R subunits, and C subunits purified from WT cells. As compared to WT R subunits, only 1/6 as much mutant R subunit was required to reassociate with and suppress 50% of C subunit activity, at equilibrium. NaSCN activates cAMP-dependent kinase of both cell types by causing the holoenzyme to dissociate. In comparison with WT, a 2-fold higher concentration of NaSCN is required to maximally activate the kinase in mutant extracts. Both the reassociation result and the increased resistance of the mutant enzyme to a nonspecific dissociating agent strongly suggest that the mutant R subunit binds C subunit more tightly than does the WT R subunit. This interpretation raises the possibility that increased R-C subunit binding affinity in the mutant cell is responsible for the increased Ka for activation by cAMP of the mutant holoenzyme, and thus for the decreased potency of cAMP in regulating intact mutant cells.